2006
DOI: 10.1681/asn.2005101040
|View full text |Cite
|
Sign up to set email alerts
|

Renal Phenotypes Related to Hepatocyte Nuclear Factor-1β (TCF2) Mutations in a Pediatric Cohort

Abstract: The hepatocyte nuclear factor-1␤ encoded by the TCF2 gene plays a role for the specific regulation of gene expression in various tissues such as liver, kidney, intestine, and pancreatic islets and is involved in the embryonic development of these organs. TCF2 mutations are known to be responsible for the maturity-onset diabetes of the young type 5 associated with renal manifestations. Several observations have suggested that TCF2 mutations may be involved in restricted renal phenotypes. Eighty children (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
205
2
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(245 citation statements)
references
References 24 publications
(31 reference statements)
28
205
2
10
Order By: Relevance
“…Only one of them developed diabetes in the years after diagnosis of renal disease. Although renal manifestations secondary to mutations HNF1B encompass a wide clinical spectrum, the absence of cysts observed in one proband is very rare (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Only one of them developed diabetes in the years after diagnosis of renal disease. Although renal manifestations secondary to mutations HNF1B encompass a wide clinical spectrum, the absence of cysts observed in one proband is very rare (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Earlier reports of individuals with the same or similar microdeletions have emphasized that these individuals do not have cognitive impairment or a neurological phenotype. 6 However, three of the patients with deletions in 17q12 in our cohort had features of neurological involvement: two patients had speech delay and one patient had moderate-to-severe mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of 17q12, including the HNF1b (hepatocyte nuclear factor 1-beta also known as transcription factor 2, MIM 189907) gene, are associated with maturity onset diabetes of the young type 5 (MODY5), as well as with cystic renal disease, renal dilations, pancreatic atrophy, and liver abnormalities. [2][3][4][5][6] Earlier reports of this contiguous gene deletion syndrome involving HNF1b have suggested that cognitive impairment is not part of the phenotype conveyed by these deletions. Mefford et al 6 have reported that recurrent deletions in this region spanning 1.8 Mb are one of the few examples of contiguous gene deletion syndromes that present without mental retardation.…”
Section: Introductionmentioning
confidence: 99%
“…(73) O envolvimento renal aparenta ser heterogéneo, com um perfil tubulointersticial na apresentação, e com um declínio progressivo da função renal ao longo do tempo, na ausência de nefropatia diabética. É possível observar-se também atrofia pancreática, anormalidades do trato genital feminino e níveis da função hepática anormais entre os indivíduos afetados.…”
Section: Mody5unclassified
“…A ausência de história familiar de doença renal ou diabetes não deve interferir na decisão de testar geneticamente, pois as mutações de novo são relativamente frequentes. (73) Tratamento A baixa sensibilidade à insulina de indivíduos MODY5 sugere um sensibilizador da insulina, tal como a metformina ou a pioglitazona, como fármaco oral de eleição.…”
Section: Mody5unclassified